Faith x Healing: The relationship between religion and improved prognosis in palliative care patients (International Seven Journal of Multidisciplinary, 2023)
It is well known that coping with chronic illness has a direct impact on the patient's psychological state. In this way, faith, whether religious or not, is an ally in improving the negative symptoms caused by the patient's vulnerable condition. Studies show that such positivity works as a source of strength for patients, giving them hope that the proposed treatment can be effective. To this end, this work seeks to relate the improvement in the healing of physical problems with spiritual help, proposing a discussion between religion and science. The topic will be approached through reviews of existing literature, as well as films, documentaries and popular beliefs. This work aims to understand the relationship between belief and the physical and psychological improvement of patients in a palliative state.